2017
DOI: 10.1103/physreva.95.032106
|View full text |Cite
|
Sign up to set email alerts
|

Causal evolution of wave packets

Abstract: Drawing from the optimal transport theory adapted to the relativistic setting we formulate the principle of a causal flow of probability and apply it in the wave packet formalism. We demonstrate that whereas the Dirac system is causal, the relativistic-Schrödinger Hamiltonian impels a superluminal evolution of probabilities. We quantify the causality breakdown in the latter system and argue that, in contrast to the popular viewpoint, it is not related to the localisation properties of the states.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 61 publications
(131 reference statements)
0
33
0
Order By: Relevance
“…The first application of the presented theory to the study of causality in quantum theory is discussed in details in [21]. Therein, we focus on the wave packet formalism, which is in common use in atomic, condensed matter [53] and particle physics [12], as an approximation to complicated QFT problems.…”
mentioning
confidence: 99%
“…The first application of the presented theory to the study of causality in quantum theory is discussed in details in [21]. Therein, we focus on the wave packet formalism, which is in common use in atomic, condensed matter [53] and particle physics [12], as an approximation to complicated QFT problems.…”
mentioning
confidence: 99%
“…Furthermore, the quantum measurement effectuates a dramatic change on particle's dynamics. In consequence, although several formal results [13][14][15][16][17][18] suggested that quantum wave packets can propagate superluminally, it was unclear whether it implies operational faster-than-light communication (cf. for instance [16] vs [19] or a more recent work [20]).…”
mentioning
confidence: 99%
“…Subsequently, we briefly sketch the rudiments of noncommutative geometry à la Connes [4]. Next, we discuss the notion of causality suitable in this context, summarising the outcome of our recent works [18][19][20][21][22][23][24][25][26]. Finally, we explain how the presumed noncommutative structure of spacetime extorts a modification of the axioms of quantum field theory and thus might yield empirical consequences.…”
Section: Introductionmentioning
confidence: 99%